Proyecto de creación de una sala de bolos en el sur de la ciudad de Guayaquil - Layana Cevallos, Olga Elizabeth (2009)
The project consists on the construction of a new center of distraction in the South sector of the city of Guayaquil, this idea is born for the emergence of a potential market in this sector due to the great change that this having the City at the moment, this market not yet place setting possesses a great demand for what the acceptance for a center of this type would be really successful. The main objective is to mark the difference in this type of business, giving a great turn to it with respect to distraction, when offering a project full with strategies and details to offer them a novel place, with tip technology, with services that nobody but he/she will have them as billiards tables, bar, you scheme of video games, all this in a single place and not so far, because many of the inhabitants of the south that you/they like of this sport have to be transported until the north of Guayaquil to be able to enjoy this sport being exposed to the danger of the delinquency. The problem basically consists in that given the lack of local of entertainment of this type, the current youth doesn't have places where to enjoy healthy amusement where they can channel all her energy in an appropriate atmosphere, practicing activities that stimulate her mind and her body in the best in the ways like you/he/she is it to practice a sport. The purpose of the project is basically guided to cover the deficiencies that he/she has the current offer of this service in the city, the same ones that motivate the development of this study, fomenting to the tourism and development of the city and at the same time changing the perception that you/they had people of the South of the city.